New product deployment: The moderating influence of economic institutional context - Shinkle, George A.; McCann, Brian T. (Strategic Management Journal, 2014)
We compare the determinants of new product deployment across transition and nontransition economy environments to show the importance of variance in economic institutional context. We argue that the expected positive relationships of institutional development, resource levels, and competitive pressure to new product deployment all weaken in transition economy contexts. Hypotheses are tested with survey data of over 7,000 firms in 7 industries from 33 countries. Copyright © 2013 John Wiley & Sons, Ltd .